2021
DOI: 10.3390/cancers13030456
|View full text |Cite
|
Sign up to set email alerts
|

CD137+ T-Cells: Protagonists of the Immunotherapy Revolution

Abstract: The CD137 receptor (4-1BB, TNF RSF9) is an activation induced molecule expressed by antigen-specific T-cells. The engagement with its ligand, CD137L, is capable of increasing T-cell survival, proliferation, and cytokine production. This allowed to identify the CD137+ T-cells as the real tumor-specific activated T-cell population. In fact, these cells express various TCRs that are specific for a wide range of tumor-derived peptides, both shared and neoantigenic ones. Moreover, their prevalence in sites close to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 154 publications
(178 reference statements)
0
9
0
Order By: Relevance
“…In addition, the CD3 + CD137 + cell subset was analysed, as these cells are regarded as anti-tumour effector T cells. 22 During CDK4/6i treatment, a trend of increased CD137 expression was observed for CD3 + cells ( p =0.07), but most importantly, CD8 + CD137 + cell levels significantly increased ( p <0.01). These results suggest that CDK4/6i treatment favours the overall activation of both subsets of CD3 + effector cells involving distinct co-stimulatory mechanisms.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, the CD3 + CD137 + cell subset was analysed, as these cells are regarded as anti-tumour effector T cells. 22 During CDK4/6i treatment, a trend of increased CD137 expression was observed for CD3 + cells ( p =0.07), but most importantly, CD8 + CD137 + cell levels significantly increased ( p <0.01). These results suggest that CDK4/6i treatment favours the overall activation of both subsets of CD3 + effector cells involving distinct co-stimulatory mechanisms.…”
Section: Resultsmentioning
confidence: 91%
“…Recently, CD3 + CD137 + T cells have been shown to play a fundamental role in efficacious anti-tumour immunity. The CD137 receptor (4-1BB, TNFRSF) is a member of the tumour necrosis factor receptor (TNFR) family that has a tumour-specific activation function 22 and is expressed by CD8 + and CD4 + T cells upon activation. Indeed, these cells have attracted particular interest regarding their potential role in various immunotherapy strategies owing to their unique ability to kill tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…CD137 + CD8 + T cells are believed to be the tumor‐infiltrating lymphocytes (T TIL ) population that promises the better clinical outcome. [ 38 ] Isolation and ex vivo expansion of the CD137 + , CD8 + T cell population is adopted in clinical trial as a promising strategy that enhances the efficacy of the adoptive T cell transfer against metastatic melanoma. [ 39 ] To test if our platform can promote generation of CD137 + CD8 + T cells, we first cultured the CD8 + T cells on AR1 or AR7 substrate for 6 days, then the obtained T cells were co‐cultured with human cervical carcinoma (HeLa cells) in a regular culture dish for another 7 days.…”
Section: Resultsmentioning
confidence: 99%
“…CD137 expression on CD8 + T cells is considered as tumor infiltrating lymphocytes acquiring the effector T cells phenotype and promises the better clinical outcome. [38][39][40] Isolation and ex vivo expansion of the CD137 + , CD8 + T cell population is a key to enhance the efficacy of the adoptive T cell transfer. [39] Finally, up-regulated expression of CD137 on CD8 + T cells co-cultured with human cervical carcinoma demonstrated a great potential of the AuNR platform for activation and ex vivo expansion of T cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we showed that CD39 + memory Tconv TILs, like circulating CD39 + memory Tconv, contained high proportions of CD28 + cells. CD137 receptor, upregulated in T cells following activation [ 30 ], was associated, when expressed in CD8 and CD4 TILs, with clinical response to ICB [ 31 ]. In the circulation, CD137 expression in CD8, but not in CD4 T cells, was predictive of clinical responses [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%